Sabiston essentials of surgery - Sabiston, David C.; Sabiston, David C., 1924-; Lyerly, H. Kim. (Philadelphia : W.B. Saunders, 1994)
this book have been written with the specific goal of providing medical students a consise text that is sufficiently detailed to fulfill the requirements of surgery courses in medical schools.
this book content homeostasis -- shock : causes and management of circulatory collapse -- surgical aspects of diabetes mellitus -- anesthesia-- trauma -- transplantation-- the esophagus-- the stomach and duodenum--n the spleen -- hernias-- the skin-- the arterial system the lung pleura and chest wall-- the heart.
surgery. include index.
Includes bibliographical references and index.
All age.
Keywords: Surgery